2017
DOI: 10.1158/1055-9965.epi-17-0428
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Incidence of Testicular Cancer: A 42-Year Follow-up of Swedish Men between 1970 and 2011

Abstract: Background Given current drug-policy reforms to decriminalize or legalize cannabis in numerous countries worldwide, it is critically important to understand the potential impacts of cannabis use on the development of cancer. The current study aims to assess the relation between cannabis use and the development of testicular cancer. Method The current study relied on a population-based sample (n = 49 343) of young men aged 18–21 years who underwent conscription assessment for Swedish military service in 1969–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 31 publications
2
40
1
Order By: Relevance
“…While interesting, it must be noted that these comparisons were made using data from only three studies, which contained data primarily collected from the United States of America in the 1990s. Similar examination of testicular cancer development and cannabis use was also explored in the same large Swedish conscription study (49,343 individuals) as mentioned above [59]. These data also demonstrated that there was no association between lifetime ever-use of cannabis and the development of testicular cancer.…”
Section: Impact On Cancer Developmentsupporting
confidence: 63%
“…While interesting, it must be noted that these comparisons were made using data from only three studies, which contained data primarily collected from the United States of America in the 1990s. Similar examination of testicular cancer development and cannabis use was also explored in the same large Swedish conscription study (49,343 individuals) as mentioned above [59]. These data also demonstrated that there was no association between lifetime ever-use of cannabis and the development of testicular cancer.…”
Section: Impact On Cancer Developmentsupporting
confidence: 63%
“…Hirao-Suzuki (2019) showed that Δ9-THC increases fatty acid 2-hydroxylase (FA2H) expression in human breast cancer cells. Murphy et al, (2019) have assumed that cannabis use was associated with significantly lower sperm concentration and Callaghan et al, (2011) recently found a link between cannabis consumption and testicular cancer. However, some studies have postulated that cannabis inhibited tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible line of investigation could be the use of cannabis as risk factor for testicular cancer. Recent evidence suggests that regular and prolonged use of TCH could be a risk factor to develop germ cell tumors, especially the nonseminoma variants 49,50 . An increase in Marijuana use was observed in our country in the last two decades; eventually boosted by the Cannabis market regulation since 2015 51 .…”
Section: Testicular Cancermentioning
confidence: 99%